Perceptions on the inclusion of published Filipino Wattpad stories in the school library setting - Reyes, Gillian P. (School of Library and Information Studies, University of the Philippines Diliman, 2016)
The medium and distribution of Young Adult Literature has changed with the advent of the Internet and independent writers. They have found free platforms to which they can share their works and garner a huge audience. Wattpad is one of these platforms and is the most famous in the country today. It is because of this that this study focuses on the current perceptions on Wattpad in the academic setting. It is also the objective of this study to find out the implications of these perceptions to the collection development policy of a school library. The guidelines for the study are supported by Reeve and Hakel. In order to see development in a brand of literature, there should be factors of motivation, cognition, and psycho-social patterns within individuals and groups. It is also supported by the framework that guarantees all opinions are to be accounted for. Two discussion groups of twelve students have been asked various questions in order to fully express their interests. Discussion groups for the teachers had also been done to ensure an authoritative quality to the subject of Wattpad as a tool for teaching. The study explores the perceptions of the students, teachers, and librarians at the Siena College of Taytay with regards to Wattpad. Students, while having a huge interest in Wattpad, have been restricted to access these materials due to the lack of guidelines. An authoritative opinion on the matter had been established by the English and Filipino teachers and see Wattpad as both a beneficial and harmful tool to teach the students. The librarian further gave an opinion that Wattpad should undergo strict evaluation before being included in the school library collection.